Fatigue life and fracture evolution of small-hole specimens by laser shock processing. (November 2020) - Jiang, Yinfang; Wang, Sili; Jiang, Wenfan; Gan, Xuedong; Hua, Cheng; Qi, Hongfei; Zhao, Yong; Huang, Jianyun
Highlights: Small energy laser shock processing for small-hole samples with thickness effects. Fatigue gain and fracture mechanism under high stress levels. Fracture morphology, stress distribution and its relationship with fatigue life. Abstract: The fatigue life and fracture characteristics of aluminum alloy small-hole specimens by laser shock processing (LSP) at different external loads were investigated. When the maximum load was 165.8 MPa, 195 MPa and 275.4 MPa, the median fatigue life gain by LSP was 3.77–4.21 times, 2.68–3.02 times and 1.77–2.20 times, respectively. The plastic deformation zone and residual stress distribution produced by LSP can restrain or control the initiation and propagation direction of cracks. It has been observed that the resulting fracture evolution depends on the applied external load. The stress simulation method, fracture morphology analysis are also used to establish the residual stress distribution, the crack propagation mode and its corresponding relationship with fatigue gain.